2015
DOI: 10.1038/emm.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin: a central GABAergic synapse organizer

Abstract: Gephyrin is a central element that anchors, clusters and stabilizes glycine and γ-aminobutyric acid type A receptors at inhibitory synapses of the mammalian brain. It self-assembles into a hexagonal lattice and interacts with various inhibitory synaptic proteins. Intriguingly, the clustering of gephyrin, which is regulated by multiple posttranslational modifications, is critical for inhibitory synapse formation and function. In this review, we summarize the basic properties of gephyrin and describe recent find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 117 publications
(146 reference statements)
2
113
0
1
Order By: Relevance
“…The reigning model of NLGN function at inhibitory synapses purports that the interaction of gephyrin with NLGN2 via its gephyrin-binding domain enables the recruitment of GABA A receptors to the synapse (Choii and Ko, 2015; Tyagarajan and Fritschy, 2014). However, there have also been reports of gephyrin-independent mechanisms of GABA A receptor enrichment at inhibitory synapses (Lévi et al, 2004; Kneussel et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reigning model of NLGN function at inhibitory synapses purports that the interaction of gephyrin with NLGN2 via its gephyrin-binding domain enables the recruitment of GABA A receptors to the synapse (Choii and Ko, 2015; Tyagarajan and Fritschy, 2014). However, there have also been reports of gephyrin-independent mechanisms of GABA A receptor enrichment at inhibitory synapses (Lévi et al, 2004; Kneussel et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that NLGN2 functions through a direct interaction on its cytoplasmic tail with gephyrin, a scaffold protein thought to be essential for stabilizing glycine and GABA A receptors at inhibitory synapses (Choii and Ko, 2015; Tyagarajan and Fritschy, 2014). In addition, it has been proposed that collybistin, a brain-specific guanine nucleotide exchange factor (GEF), helps regulate the localization of gephyrin, and that NLGN2 is a specific activator of collybistin via a direct interaction at the proline rich region in its cytoplasmic tail (Kins et al, 2000; Poulopoulos et al, 2009; Soykan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Excitatory and inhibitory synapses are identified postsynaptically by distinct neurotransmitter receptor, scaffolding protein, and adhesion molecule repertoires (Craig and Kang, 2007; Sheng and Kim, 2011; Ziv and Fisher-Lavie, 2014). Postsynaptic factors like Neuroligin 2 (Graf et al, 2004), Gephyrin (Choii and Ko, 2015), and Slitrk3 (Takahashi et al, 2012) organize inhibitory GABAergic synapses while LRRTMs organize excitatory synapses (Siddiqui et al, 2013; de Wit et al, 2009, 2013). Thus, postsynaptic regulation can occur by differential modulation of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to function as a scaffold at inhibitory synapses, analogous its function to that of PSD-95 at glutamatergic synapses. It can bring GABA A receptors and stabilize them in the inhibitory synapses (Essrich et al, 1998; Kneussel et al, 1999; Jacob et al, 2005; Choii and Ko, 2015). Studies showed that the modulation of gephyrin was accompanied by changes in the clustering and function of GABA A receptor (Petrini et al, 2014).…”
Section: Discussionmentioning
confidence: 99%